Efektivitas Latihan Ketepatan Servis Atas dengan Kick Pad vs Bola Gantung Sepak Takraw - Male, Salpin; Kadir, Suprianto; Duhe, Edy Dharma Putra; Haryanto, Arief Ibnu (Institut Teknologi Bandung, 2024)
Training using kick pads and hanging balls are tools that are often used to improve the accuracy of top serves in the sport Sepak Takraw. Using these two tools simultaneously helps players develop control, strength and accuracy of serves which are very important in matches. The aim of this research is to find out which tool is most appropriate to use, between a kick pad or a modified hanging ball to improve the accuracy of the top serve in the Sepak Takraw sport. This research used an experimental research method of two group pre test - post test design using research subjects of Sepak Takraw extracurricular students at State High School (SMA) 4 Gorontalo, totaling ten students, with the determination of groups for the kick pad and hanging ball groups carried out randomly. The instrument in this research uses a standardized Sepak Takraw service accuracy test with several sides numbered in accordance with the provisions of the instrument. The results of this research generally show that the use of these two tools can increase the accuracy of the top serve in the Sepak Takraw sport, but in terms of average percentage, the group that uses the kick pad is superior. The conclusion from this research is clear that the use of a kick pad tool is more recommended than a hanging ball modification tool, so it is necessary to carry out another research to find out a better tool to increase the accuracy of the top serve.